Pulsed amperometry for anti-fouling of boron-doped diamond in electroanalysis of β-agonists: Application to flow injection for pharmaceutical analysis - Karuwan C. (2014)
This work presents the construction and application of boron-doped diamond (BDD) thin film electrode as sensor for the determination of three β-agonists, viz. salbutamol, terbutaline and clenbuterol. Although well-known as a chemically inert material, BDD film however shows fouling in detection of these compounds using fixed-potential mode amperometry. A suitable waveform for pulsed amperometric detection (PAD) was developed and used to determine the agonist compounds. It was seen that the developed PAD significantly refreshed the BDD surface for long-term detection in flow injection analysis. Linear working ranges were 0.5-100 μM, 1.0-100 μM and 0.5-50 μM for salbutamol, terbutaline and clenbuterol, respectively. The developed PAD-BDD system was applied to successfully determine salbutamol and terbutaline in commercial pharmaceutical products. The methods were validated with a capillary electrophoresis method. © 2006 by MDPI.